2018
DOI: 10.25159/0256-8845/3849
|View full text |Cite
|
Sign up to set email alerts
|

Cadre Deployment Policy and its Effects on Performance Management in South African Local Government: A Critical Review

Abstract: The change from a politically-sanctioned racial segregation opened support of another popularity based administration which was an overwhelming procedure at all levels. In South Africa, the positive policies to turnaround the economy of the country came along with cadre deployment policy which advocates for ANC party loyalists to occupy a prominent position in the public sector. This political patronage via state jobs leads to poor institutional quality or performance of the nation as a whole. Focusing on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 11 publications
5
21
0
Order By: Relevance
“…Masiya et al (2019) state that conflicts between managerial officials and elected officials in certain instances emerge because managerial officials are either unwilling or unable to share decision-making power with elected representatives, while politicians often encroach on officials' sphere of responsibility. In closely related observations, Tshishonga (2014) and Shava and Chamisa (2018) have argued that South Africa pursues a politicised bureaucratic model which is anchored in the cadre deployment strategy of the African National Congress (ANC). This involves the appointment of party loyalists to public institutions, purportedly to enhance public reporting lines and ensure that the institution stays true to the party's mandate as endorsed by voters.…”
Section: Discussionmentioning
confidence: 99%
“…Masiya et al (2019) state that conflicts between managerial officials and elected officials in certain instances emerge because managerial officials are either unwilling or unable to share decision-making power with elected representatives, while politicians often encroach on officials' sphere of responsibility. In closely related observations, Tshishonga (2014) and Shava and Chamisa (2018) have argued that South Africa pursues a politicised bureaucratic model which is anchored in the cadre deployment strategy of the African National Congress (ANC). This involves the appointment of party loyalists to public institutions, purportedly to enhance public reporting lines and ensure that the institution stays true to the party's mandate as endorsed by voters.…”
Section: Discussionmentioning
confidence: 99%
“…Since its adoption by the ANC in 1998, it is justifiable to argue that cadre deployment policy has done more harm than good concerning ethical governance. A study by Shava and Chamisa (2018) confirmed that cadre deployment exacerbated problems related to corruption, poor procurement systems, wasteful expenditure, and the deteriorating state of local government. Noting the scourge of cadre deployment within government institutions, Professor Chris Landsberg, the head of the Politics and Foreign Policy Department at the University of Johannesburg, cited the need to depoliticize and professionalize the diplomatic services.…”
Section: B the Cost Of Cadre Deployment On Governance In Local Municipalitiesmentioning
confidence: 99%
“…Mkhongi (2013) argued that the ANC uses the phrase cadre policy or deployment with the notion that the power of any revolutionary organization is determined not only by its numbers but also by the quality of its cadres. Shava and Chamisa (2018) argued that cadre deployment pushed for the appointment of ANC party loyalists to highranking positions in the public sector. This political favoritism, which was carried out through state positions, resulted in poor performance in government institutions and the country as a whole.…”
Section: A the Concept Of Cadre Deployment And Reasoning Behind Itmentioning
confidence: 99%
See 2 more Smart Citations